2005
DOI: 10.1097/00000542-200510000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Role for Cyclooxygenase 2 in the Development and Maintenance of Neuropathic Pain and Spinal Glial Activation

Abstract: Spinal cyclooxygenase 2 mediates the development but not the maintenance of neuropathic pain and glial activation in rats. Peripheral cyclooxygenase 2 plays a part in the maintenance of neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 34 publications
1
34
0
1
Order By: Relevance
“…started 7 days after ligation partially reversed NP but not glial activation. This data suggests that spinal prostaglandin production by spinal COX-2 plays a pivotal role in the development of neuropathic pain, however, it is not critical for the maintenance of such pain [32].…”
Section: Meloxicam In Nerve Damage Modelsmentioning
confidence: 87%
See 4 more Smart Citations
“…started 7 days after ligation partially reversed NP but not glial activation. This data suggests that spinal prostaglandin production by spinal COX-2 plays a pivotal role in the development of neuropathic pain, however, it is not critical for the maintenance of such pain [32].…”
Section: Meloxicam In Nerve Damage Modelsmentioning
confidence: 87%
“…Distribution and metabolism of celecoxib in rats is similar to in humans through a single metabolic pathway. Celecoxib has analgesic and anti-inflammatory effects in patients with rheumatoid arthritis and no effect on COX-1 activity at therapeutic plasma concentrations [25,31,32]. In past studies, efficacy of several selective COX-2 inhibitors using chemically-and physically-induced peripheral nerve injury in animal research models has been reported.…”
Section: Discussion Study 1: Indomethacin and Celecoxibmentioning
confidence: 99%
See 3 more Smart Citations